La più antica testimonianza sul teatro a Siracusa? Nota a Diom. GL I p. 486, 27-31 Keil e [Prob.] Comm. in Verg. Buc. et Georg. p. 324, 23-325, 3 Hagen - Favi, F (Loescher Editore, 2017)
It is generally believed that two passages in Diomedes and ps.-Probus testify to the existence of a theatre in Syracuse at the time of the Deinomenid tyrants, Hiero and Gelo. It is, however, more likely that the Hiero and Gelo of these grammatical sources are to be identified with the third-century tyrants Hiero II and Gelo II. Moreover, the abovementioned passages belong to a group of testimonia on the origins of bucolic poetry, and in the same vein they manipulate both mythological and historical material in order to achieve their primary goal, without aiming for an historically verifiable reconstruction.